PELATIHAN PEMBUATAN SABUN MANDI PADAT UNTUK BINAAN PANTI ASUHAN YAYASAN SITI FATIMAH PANDAAN - Heny Dewajani; Ernia Novika Dewi; Mufid; Imron Rosyidi (Jurnal Pengabdian kepada Masyarakat, 2022)
Yayasan Yatim Piatu Siti Fatimah Pandaan, located in Nogosari village 2 km from Pandaan sub-district, was established in 1984 and has a total of 117 foster children. In order to improve the creativity and skills of foster children, it is necessary to hold applicative training. Politeknik Negeri Malang as one of the educational institutions in carrying out its function, namely the Tri Dharma of Higher Education is obliged to carry out community service (Pengabdian kepada masyarakat, PkM) through various forms of activities. The Department of Chemical Engineering in collaboration with the Yayasan Yatim Piatu Siti Fatimah Pandaan provided training in making solid bath soap. Due to the Covid-19 pandemic, the PkM implementation was held online on October 2, 2020, attended by school representatives and a team of lecturers from the Chemical Engineering Department. By enforcing the health protocol, the lecturer team submitted video tutorials, product samples and modules for making solid bath soap to the Yayasan Yatim Piatu Siti Fatimah Pandaan. The explanation about creating of bath soap was carried out online through google meet. With the implementation of this PkM, it is hoped that will be useful in providing knowledge and skills for the Yayasan Yatim Piatu Siti Fatimah Pandaan.